Model Pembelajaran Konstruktivistik Mata Pelajaran Bahasa Arab (Menulis) Dengan Media صورة - Mohammad Hasan Rasidi (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Referring to the Arabic language curriculum subject Permenag number: 2 of 2008 which states that; Arabic language learning which include the four language skills: listening (الأستماع), talk (الكلام), reading(القراءة), and writing(الكتابة). PTK is the MAM 02 Pondok Modern Paciran Lamongan. Arabic Language subject, Competency Standards, class XII / IPA the first half, with the number of students 22 children, in the academic year 2015/2016. Data collected through observation notes and the results of evaluations conducted since the beginning of the study until the third cycle along with collaboration partners. In the reflection of the data analysis process, problems and obstacles encountered, followed by a reflection of the impact of the implementation of the actions performed. One important aspect of reflection is the evaluation of the success and achievement of goals. The results showed that the students' ability to understand the material using Konstruktivistik learning model is satisfactory. Overall the results showed an increase in both activity, cooperation, as well as student achievement,